2015
DOI: 10.1002/lary.25415
|View full text |Cite
|
Sign up to set email alerts
|

Voice and respiratory outcomes after permanent transoral surgery of bilateral vocal fold paralysis

Abstract: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…The authors considered various respiratory as well as objective and subjective voice‐quality parameters . The results of this study showed an expected and statistically significant improvement of the key spirometric parameters (e.g., PEF and PIF) 6 months after the surgery, which was accompanied by an objective worsening of the voice quality . Notably, the patients included in that study showed an already compromised voice quality before surgery, a characteristic that we also observed in our study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The authors considered various respiratory as well as objective and subjective voice‐quality parameters . The results of this study showed an expected and statistically significant improvement of the key spirometric parameters (e.g., PEF and PIF) 6 months after the surgery, which was accompanied by an objective worsening of the voice quality . Notably, the patients included in that study showed an already compromised voice quality before surgery, a characteristic that we also observed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, Nawka et al published the results of a study concerning the evaluation of the endoscopic glottic enlargement within a postoperative follow‐up period of 6 months. The authors considered various respiratory as well as objective and subjective voice‐quality parameters . The results of this study showed an expected and statistically significant improvement of the key spirometric parameters (e.g., PEF and PIF) 6 months after the surgery, which was accompanied by an objective worsening of the voice quality .…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…If the symptoms cannot be relieved by conservative therapies, these established, safe and long‐term effective microlaryngoscopic and transcervical medialisation procedures were shown to significantly improve the voice and quality of life . While tracheostomy is still the choice in life‐threatening BVFP, subsequent implementation of surgical glottal enlargement should be considered for decannulation and closure of the tracheostoma . Alternative methods to regain respiratory functionality after BVFP onset by means of more physiological treatments include the development of laryngeal pacemakers, which have, in contrast to current surgical therapies, the potential to improve respiration while preserving voice quality …”
Section: Discussionmentioning
confidence: 99%